Optimization of arsenic removal from water using novel renewable adsorbents derived from orange peels - Roya Sadat Neisan; Noori M. Cata Saady; Carlos Bazan; Sohrab Zendehboudi (Waste Management Bulletin)
This study developed activated carbon from orange peels (ACOP) and modified ACOP with titanium dioxide (TiO2) (ACOP-TiO2), focusing on optimizing the adsorption capacity of ACOP-TiO2 for arsenic removal from water. The developed adsorbent (ACOP-TiO2) was prepared and characterized by Scanning electron microscopy (SEM), Energy dispersive X-ray analysis (EDS), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), surface area analysis, and elemental analysis. The Brunauer-Emmett-Teller (BET) test demonstrated that the modification increased the surface area of ACOP-TiO2 by 2.55 times greater than ACOP. Adsorption experiments were conducted using synthetic aqueous solutions of arsenic (As(V)), and the response surface methodology (RSM) incorporating central composite design (CCD) was employed for experimental optimization. The results indicated that ACOP-TiO2 demonstrated efficient arsenic removal, with optimal pH identified at approximately 4.2. Increasing adsorbent dosage (0.025–0.4 g in 50 mL solution, corresponding to 0.5–8 g L-1) positively influenced adsorption efficiency, while initial arsenic concentration (10–60 mg L-1) directly correlated with adsorbent capacity, with a predicted optimum concentration of 50 mg L-1. Contact time (0.4–6 h) exhibited minimal impact on adsorbent capacity within the experimental timeframe. Under the conditions of pH 4.2, an initial arsenic concentration of 50 mg L-1, an adsorbent dose of 3.3 g L-1 (0.165 g adsorbent/50 mL solution), and a contact time of 4.8 h, the maximum adsorbent capacity in arsenic removal for ACOP-TiO2 was 10.91 mg g−1. The intra-particle diffusion kinetic model and Temkin isotherm best described arsenic adsorption onto ACOP-TiO2. This research contributes valuable insights into utilizing agricultural waste for water treatment, offering a sustainable and economical solution for arsenic removal.